For a Vague Writing:: contemplation and (re)generation - Fernandes, Ciane; Dodd, Deborah; Pizarro, Diego; Rosa Santana, Eduardo Augusto; Scialom, Melina (Revista Brasileira de Estudos da Presença, 2025)
This article is a reflective dialog between artists/educators/researchers from various Brazilian institutions integrating ecoperformances and Somatics in Artistic Practice as Research. A vagal movement as writing, based on the contemplation of the generative impulse present in ecoperformative practices, shifts the group from an environmental immersion to a textual immersion. The attentional supports - somatic rest, dynamic pause, and tensional contemplation - attune with diverse immersive contexts - geoecological performance, virtual ecoperformance, staging and ecoperformative news. There is a summoning to the field of ecoperformance and Somatics, so the research’s written outwarding is guided by the mobilizing principles of the somatic-performative practice, within an ecocentric ethics.